2010
DOI: 10.1007/s00277-009-0869-5
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of the endothelial receptor tyrosine kinase Tie2 correlates with leukemic blast burden and outcome after allogeneic hematopoietic stem cell transplantation for AML

Abstract: Angiogenesis plays an important role in the growth and viability of hematologic malignancies. Emerging data suggest a crucial involvement of the endothelial-specific Tie2 receptor and its antagonistic ligand Angiopoietin-2 (Ang-2) in this process. The purpose of this study was to elucidate whether the soluble domain of the Tie2 receptor (sTie2) predicts outcome in patients with acute myeloid leukemia (AML) undergoing allogeneic hematopoietic stem cell transplantation (HSCT). Serum levels of sTie2 and Ang-2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Firstly, the risk of serious complications early after allotransplantation is associated with the preconditioning serum profile of immunoregulatory and angioregulatory mediators, and the same seems to be true for systemic levels of endothelial cell-derived adhesion molecules (Lindås et al 2014; Reikvam et al 2012a). Secondly, an association between serum levels of angioregulatory Angiopoietin-2/Tie2 and relapse-free survival was described for a selected group of high-risk patients with only 17 out of 90 patients being in complete remission prior to transplantation (Koenecke et al 2010; Kümpers et al 2008). These patients are thus not comparable to our unselected patients.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the risk of serious complications early after allotransplantation is associated with the preconditioning serum profile of immunoregulatory and angioregulatory mediators, and the same seems to be true for systemic levels of endothelial cell-derived adhesion molecules (Lindås et al 2014; Reikvam et al 2012a). Secondly, an association between serum levels of angioregulatory Angiopoietin-2/Tie2 and relapse-free survival was described for a selected group of high-risk patients with only 17 out of 90 patients being in complete remission prior to transplantation (Koenecke et al 2010; Kümpers et al 2008). These patients are thus not comparable to our unselected patients.…”
Section: Resultsmentioning
confidence: 99%
“…Given that VEGF is a potent pro‐angiogenic factor, VEGF‐mediated shedding of Tie2 appears to promote the switching from vascular quiescence to angiogenesis through the disruption of pre‐existing transassociation of Tie2 at EC–EC contacts and sTie2‐dependent modulation of Ang/Tie2 signalling. Importantly, serum sTie2 levels are elevated in patients with malignancies, 7–9 cardiovascular diseases, 10–12 and inflammatory bowel diseases, 13 suggesting that sTie2‐dependent modulation of endothelial behaviour is involved in the pathophysiology of these diseases. As VEGF levels are increased in the skin and sera of SSc patients, 14,15 sTie2 may serve as a marker of endothelial activation in SSc.…”
Section: Introductionmentioning
confidence: 99%
“…Koenecke, agreed with us but he used ELISA for detection of Angiopoietin 2 and TIE2. He found that Angiopoietin 2 at 2.18 ng/mL was associated with a prognostic sensitivity of 55% and a specificity of 76% (AUC 0.64, p=0.002) and Tie2 concentration of 2.24 ng/mL was associated with a prognostic sensitivity of 69% and a specificity of 49% (AUC 0.62, p=0.01) [19].…”
Section: New Blood Vessel Formation Is a Hull Mark In Cancer Progresmentioning
confidence: 99%